On JS-Injective Rings - Zone, Zahraa Abbas; Mehdi, Akeel Ramadan (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2023)
Let be a ring. A right -module is called JS- -injective (where is any right -module) if every right -homomorphism from a submodule of J J into extends to [9]. A ring is called right JS-injective if is JS- -injective. The right JS-injective rings are studied in this paper. Many characterizations and properties of this type of rings are obtained.